Understanding variability and repeatability of enteric methane production in feedlot cattle - Beauchemin, Karen A.; Tamayao, Paul; Rosser, Christine; Terry, Stephanie A.; Gruninger, Robert (Frontiers in Animal Science, 2022)
Breeding ruminants for low methane (CH4) emissions can be permanent and cumulative, but requires a better understanding of the variability of CH4 production among animals to accurately assess low-CH4 phenotypes. Our objectives were to: 1) investigate the variation in CH4 production among and within growing beef cattle, 2) identify low-CH4 emitters, and 3) examine relationships between CH4 production and intake, feeding behavior, growth, and rumen fermentation. Crossbred beef heifers (n=77; body weight=450 kg) were allocated to 3 pens and offered a finishing diet of 90% concentrate and 10% silage (dry matter (DM) basis). The study was conducted over 3 consecutive 6-week periods (126 days). GrowSafe bunks measured individual animal DM intake (DMI) and rumen fluid was sampled orally each period. A GreenFeed system measured individual animal emissions for 2 weeks/period. Methane production was calculated by animal within period using visits that were ≥3 min with fluxes compiled into six 4-h blocks corresponding to time of day, and averaged over blocks to obtain an average daily emission for the period. Animals with <12 visits and <5 blocks were omitted for the period and animals with ≥2 periods of complete CH4 data were used in the final analysis (n=52). Animals were ranked based on CH4 yield (g/kg DMI) from low to high, and grouped as Very-low (≤10% of animals), Low (11-25%), Intermediate (26-74%), High (75-89%), and Very high (≥90%) emitters (mean ± SD, 12.6 ± 2.16). The CH4 yield was 16% less (P<0.05) for Very-low compared with Intermediate animals due to lower CH4 production (g/d, P<0.05), with no differences in DMI (P>0.05). However, the period × grouping interaction (P<0.001) for CH4 yield indicated that the ranking of animals changed over time, although there were no extreme changes in rankings. Total VFA concentration decreased as CH4 yield decreased, but molar proportions of VFA remained unchanged, suggesting lower extent of ruminal digestion rather than a shift in fermentation. There were no differences in feeding behavior or average daily gain among groupings (P>0.05). The between-animal coefficient of variation in CH4 yield of 17.3% enabled identification of low CH4-emmitting finishing beef cattle. However, accurate selection of low CH4-emitting animals should be based on repeated CH4 measurements over the production cycle.